UNIVERSITY RESILIENCE TO IMPROVE COMPETITIVENESS IN THE PANDEMIC ERA - ISTIQOMAH, NURUL (JOSAR (Journal of Students Academic Research), 2024)
These research purposes are: Understanding the effect of Covid-19 to Colleges of UNISBA and UNU Blitar. Describing the resilience of the Islamic Financial Management System in maintaining competitiveness in the Covid-19 pandemic era at UNISBA and UNU Blitar City. This research uses a qualitative research approach, the type of research is Case Study. The data used in extracting information are primary and secondary data with data collection methods through in-depth interviews, observation and documentation. After obtaining field data, the data is processed and analyzed using interactive analysis methods. In an effort to analysis the validity of the data, in this study also analyzed by triangulation. After analyzed by kinds of analysis data, the research showed that: Covid-19 Pandemic on both colleges between UNISBA and UNU are effected on all fields. There is high resilience in both Colleges between UNISBA and UNU Blitar City so that they can not only survive but also be able to compete in the midst of the Covid-19 pandemic.